The Relationship between Workload and Work Stress and Nurse Performance in the Emergency Installation (IGD) of Dr. M.M Dunda Limboto Hospital - Sri Aryanti Yusuf; Siti Rahma; Rachmawaty D. Hunawa (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Emergency Installations (IGD) have high work dynamics that require nurse preparedness for 24 hours, so nurse performance is an important indicator in determining service quality. Nurse performance includes quality, quantity, precision and work behavior according to professional standards. In its implementation, nurses face an excessive workload and can trigger work stress in the form of emotional pressure when providing services. This study aims to determine the relationship between workload and work stress and the performance of nurses in the Emergency Installation (IGD) of Dr. M.M Dunda Limboto Hospital. This study is a quantitative research with a cross sectional method. A sample of 31 nurses was taken using the total sampling technique. This research instrument used questionnaires of workload, work stress, and nurse performance. Bivariate analysis using the Spearman Rank test. The results showed a significant relationship between workload and nurse performance (p-Value = 0.001; r = -0.580). Meanwhile, there was also a significant relationship between work stress and nurse performance (p-Value = 0.003; r = -0.520. It is hoped that the hospital can hold a stress management program and workload management on a regular basis and create a conducive work environment to improve nurse performance.